Analisis Kesalahan Linguistik dan Kelayakan Menurut Badan Standar Nasional Pendidikan Pada Buku Keluargaku Unik BAB VI - Ilyana, Khilma Azza; Purwati, Panca Dewi; Alfiansyah, Muh. Dewangga; Prabawani, Almira Veda; Putri, Meila Cahyani; Andriani, Aprilia Devi (Innovative: Journal Of Social Science Research, 2025)
The second grade student book needs to be reviewed because it still has several errors in writing. The analysis study was carried out in four aspects, namely describing the analysis of the feasibility of the content, describing the results of the language study, describing the results of the content study, describing the results of the graphic study according to BSNP. The approach used was qualitative with the document content analysis method. Data were collected through a comprehensive study of sentences, vocabulary, and the use of spelling used in the book, which were then analyzed based on linguistic theory. The results of the study showed that this book generally meets the feasibility criteria, but there are still many shortcomings in the linguistic aspect, especially in the use of punctuation and spelling. With this analysis, the second grade book is worthy of being recommended to support learning.